Constitutive activation and oncogenicity are mediated by loss of helical structure at the cytosolic boundary of thrombopoietin receptor mutant dimers - Jean-Philippe Defour; Emilie Leroy; Sharmila Dass; Thomas Balligand; Gabriel Levy; Ian C Brett; Nicolas Papadopoulos; Céline Mouton; Lidvine Genet; Christian Pecquet; Judith Staerk; Steven O Smith; et al. (eLife, 2023)
Dimerization of the thrombopoietin receptor (TpoR) is necessary for receptor activation and downstream signaling through activated Janus kinase 2. We have shown previously that different orientations of the transmembrane (TM) helices within a receptor dimer can lead to different signaling outputs. Here we addressed the structural basis of activation for receptor mutations S505N and W515K that induce myeloproliferative neoplasms. We show using in vivo bone marrow reconstitution experiments that ligand-independent activation of TpoR by TM asparagine (Asn) substitutions is proportional to the proximity of the Asn mutation to the intracellular membrane surface. Solid-state NMR experiments on TM peptides indicate a progressive loss of helical structure in the juxtamembrane (JM) R/KWQFP motif with proximity of Asn substitutions to the cytosolic boundary. Mutational studies in the TpoR cytosolic JM region show that loss of the helical structure in the JM motif by itself can induce activation, but only when localized to a maximum of six amino acids downstream of W515, the helicity of the remaining region until Box 1 being required for receptor function. The constitutive activation of TpoR mutants S505N and W515K can be inhibited by rotation of TM helices within the TpoR dimer, which also restores helicity around W515. Together, these data allow us to develop a general model for activation of TpoR and explain the critical role of the JM W515 residue in the regulation of the activity of the receptor.